Novel methods for 3D postoperative analysis of total knee arthroplasty using 2D-3D image registration - Kim, Youngjun; Kim, Kang-Il; Choi, Jin Hyeok; Lee, Kunwoo (ELSEVIER SCI LTD, 2011)
Background: Radiographic evaluation of patients after total knee arthroplasty is an important tool for assessing the correct position of the implants and the axis of limb alignment because this will determine long-term durability of the implants. Recently, 2D-3D medical image registration methods are developed for 3D postoperative analysis of total knee arthroplasty. However, most of these techniques have focused only on knee implants. Methods: A 2D-3D medical image registration is implemented to compute the 3D positions of not only implants but also lower limb bones. The following 3D postoperative analysis methods for total knee arthroplasty are presented in this paper: (1) automatic calculation of relative angles of implants and bones, (2) assessment of external rotation angles of inserted implants, and (3) measurement and comparison of both flexion-extension gap balances. Finally these methods have been applied in five patients who underwent total knee replacements. Findings: A practical method that can evaluate the patient's knee conditions has been successfully developed. The repeatability and accuracy of 2D-3D registration were around 0.2 mm as obtained from the tests using model bones. Based on the 3D information, the novel methods of postoperative analysis were proposed and successfully applied to the patients. Interpretation: The 3D positions for both knee implants and lower limb bones can be calculated in order to perform comprehensive postoperative analyses of total knee arthroplasty. The proposed analyses of the postoperative evaluations facilitated various 3D evaluations of the status of implants, alignment of lower limb and gap balances which were not previously feasible. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: FEMORAL COMPONENT; ROTATIONAL ALIGNMENT; PATELLAR TRACKING; X-RAY; FLUOROSCOPY; KINEMATICS; SYSTEM; AXIS; CT